DISAIN KONTROLER PI DENGAN DECOUPLING PADA SISTEM KENDALI LEVEL COUPLED TANK - Muhammad Sadli (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2014)
The problems on the Coupled Tank control level is the existence of disturbance in the flow that supplies tank would make unstability response, so it could happen the cross interaction between input and output. PI control is an attractive option when the formulation of the proposed method to the Coupled Tank TITO system. PI control has the ability to maintain a steady state value of the response of the disturbance. In this study, it use Decoupling in cross interaction processes for every tank. Coupled Tank on TITO system can changes transfer function to SISO, so it can minimize the effect of interactions. The good way to design a model is consider the state on that plant, so the desired control model capable save non-linearity from TITO system. The simulations show value of percent overshoot (Mp), settling time (Ts) and steady state error (Ess), of the state of each system was 0%, 38 seconds, and 0.22%.